Pengaruh Store Atmosphere, Kualitas Layanan Dan Brand Image Terhadap Kepuasan Pelanggan Dimatahari Departemen Store Plaza Kabupaten Gresik - Rohmawati, Lilis Indah (Universitas Muhammadiyah Gresik, 2023)
Background – The progress in the economic sector so far has brought many rapid developments in the trading business sector and brought about major changes in the Indonesian retail market. Objective – This study aims to test the effect of store atmosphere, service quality and brand image on customer satisfaction at Matahari Department Store Plaza, Gresik Regency. Design / Methodology / Approach – The research method used is quantitative research methods, the types and sources of data used are primary data, and data collection techniques are carried out by distributing questionnaires. Findings – Research data were collected by distributing questionnaires to 100 respondents who visited Matahari Department Store Plaza, Gresik Regency. Research Implication – The data analysis technique used is multiple linear regression analysis. Store Atmosphere (X1) obtained t count of (4.306), while t table was (1.984) at a significant level of 5%, thus the results of statistical calculations show that partially the Store Atmophere (X1) variable is proven to have a significant effect on Matahari Department Store Customer Satisfaction. Gresik Regency Plaza. Service Quality (X2) obtained t count of (1.878), while t table was (1.984) at a significant level of 5%. Thus the results of statistical calculations show that service quality has no effect on Customer Satisfaction at Matahari Department Store Plaza Gresik Regency. Brand Image (X3) obtained t count of (1.997), while t table of (1.984) at a significant level of 5%. Thus the results of statistical calculations show that the Brand Image affects the Customer Satisfaction of Matahari Department Store Plaza, Gresik Regency. Limitations – cannot make direct observation because it is hampered by covid 19